Conformance checking of mixed-paradigm process models. Issue 102 (December 2021) - van Dongen, Boudewijn F.; De Smedt, Johannes; Di Ciccio, Claudio; Mendling, Jan
Abstract: Mixed-paradigm process models integrate strengths of procedural and declarative representations like Petri nets and Declare . They are specifically interesting for process mining because they allow capturing complex behavior in a compact way. A key research challenge for the proliferation of mixed-paradigm models for process mining is the lack of corresponding conformance checking techniques. In this paper, we address this problem by devising the first approach that works with intertwined state spaces of mixed-paradigm models. More specifically, our approach uses an alignment-based replay to explore the state space and compute trace fitness in a procedural way. In every state, the declarative constraints are separately updated, such that violations disable the corresponding activities. Our technique provides for an efficient replay towards an optimal alignment by respecting all orthogonal Declare constraints. We have implemented our technique in ProM and demonstrate its performance in an evaluation with real-world event logs. Highlights: We present the first mixed-paradigm process model conformance checking approach Alignments include constraints to replay mixed paradigm process models efficiently Optimal replay can be achieved by either allowing or disallowing constraint violation The approach is verified on three real-life event logs showing its applicability